Efektivitas Pemanfaatan Aset Wakaf Untuk Wisata Halal Sebagai Potensi Lapangan Pekerjaan - Nur Adevita; Fadhilah Fasehdiyah; Rissa Sablia Rati; Adinda Oktavia; Nur Azizah (Pusat Riset dan Inovasi Nasional, 2024)
Waqf is one of the Islamic social instruments that has a dual role, namely as a religious institution and as an economic instrument. Waqf can improve the welfare of the ummah, support government spending, and absorb labor. The author applies a descriptive qualitative approach using the literature study research method. This method involves collecting data from various literatures, especially articles from scientific journals relevant to the research topic. Halal tourism is a travel concept that fulfills the principles of Islamic sharia in every aspect. The purpose of halal tourism is to provide a vacation experience that complies with religious principles for Muslim tourists, which includes spiritual, cultural, and also their practical needs while traveling. From the research conducted, it appears that the optimization of waqf assets has great potential in creating significant employment opportunities and can reduce the unemployment rate.